Perceived influence of alcohol consumption, substance use, and mental health on PrEP adherence and condom use among PrEP-prescribed gay, bisexual, and other men-who-have-sex-with-men: a qualitative investigation - Paul A. Shuper; Thepikaa Varatharajan; David J. Kinitz; Dionne Gesink; Narges Joharchi; Isaac I. Bogoch; Mona Loutfy; Jürgen Rehm (BMC Public Health, 2022)
Abstract Background Gay, bisexual, and other men-who-have-sex-with-men (GBMSM) continue to be disproportionately affected by Human Immunodeficiency Virus (HIV). Although HIV pre-exposure prophylaxis (PrEP) offers an effective means of reducing incident HIV among this population, the HIV-preventive success of oral-based PrEP is contingent upon regimen adherence. Elevated rates of alcohol-, substance use-, and mental health-related issues among GBMSM potentially hinder PrEP-taking efforts, however the evidence for this remains mixed. Accordingly, the present study entailed a comprehensive qualitative investigation to explore PrEP-prescribed GBMSM’s perceptions surrounding the influence of alcohol, substance use, and mental health on PrEP adherence. Methods PrEP-prescribed GBMSM (age ≥ 18 years; prescribed PrEP for ≥ 3 months) were recruited from two PrEP-delivery clinics in Toronto, Canada for focus groups as part of the formative phase of an alcohol-, substance use-, and mental health-focused randomized controlled intervention trial. Focus group discussions qualitatively explored perceived strengths and barriers associated with adherence to PrEP treatment; with an emphasis on alcohol, substance use, and mental health concerns. Condom use among PrEP-prescribed GBMSM within the context of these concerns was also discussed. Results A total of five focus groups involving 35 GBMSM were conducted (4–10/group; mean age = 42.4; white = 71.4%). Although participants themselves generally reported successfully adhering to their PrEP regimens—resulting from a strong, underlying motivation for self-care—they recognized the detrimental impact that alcohol, substance use, and mental health had on adherence among their peers. In this regard, alcohol and substances were perceived as detracting from adherence only when consumption was excessive or temporally linked to PrEP dosing. Pronounced mental health issues (e.g., severe depression) were also seen as hindering adherence, although these effects were nuanced and perceived as person-dependent. Alcohol and substances were linked to condomless sex, regardless of PrEP use, and PrEP was therefore viewed as an HIV-protective ‘safety net.’ Conclusions Overall, findings suggest that PrEP adherence can often be successfully achieved in the presence of alcohol-, substance use-, and mental health-related issues. Augmenting self-care, and addressing pronounced addictions- and mental health-related concerns, may enhance PrEP treatment among GBMSM.